Pengaruh Kepuasan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Housekeeping pada PT. Telkom Property Medan - Karin Amanda; Tika Nirmala Sari (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the influence of store atmosphere, location, and promotion on consumer purchase decisions at Eiger Adventure Store Medan Marelan. The research objectives are: (1) to identify and analyze the partial influence of store atmosphere on consumer purchase decisions; (2) to identify and analyze the partial influence of location on consumer purchase decisions; (3) to identify and analyze the partial influence of promotion on consumer purchase decisions; and (4) to identify and analyze the simultaneous influence of store atmosphere, location, and promotion on consumer purchase decisions. This research applies a quantitative approach with a causal associative design. The sample consists of 120 respondents selected using accidental sampling. Data were collected through questionnaires and analyzed using multiple linear regression with partial (t) and simultaneous (F) tests. The results show that, partially, store atmosphere does not have a significant effect on purchase decisions, location has a positive and significant effect, while promotion does not have a significant effect. However, simultaneously, all three variables significantly influence consumer purchase decisions. These findings emphasize that store location plays a crucial role in influencing purchase decisions, while improvements in store atmosphere and promotion strategies are necessary to enhance consumer attraction and loyalty.